Detection of atelectasis with Lung ultrasonography in adults undergoing robot assisted laparoscopic pelvic surgeries - Aiman Shah; Shahzad Yaqoob; Nuzhat Majeed (Medical Journal of South Punjab, 2024)
Objective: to detect post-operative atelectasis in this subsets of robotic surgery patientsMethodology: Patients of age 18-70 years undergoing robot-assisted pelvic surgeries in the steep Trendelenburg position, were enrolled in the study. Mechanical ventilation was administered using 50% oxygen in air, with a tidal volume of 6 to 8 ml/kg in volume control mode, to maintain an end-tidal carbon dioxide level of 35?45 mmHg and a positive end-expiratory pressure (PEEP) of 5 cmH2O. Ultrasonographic assessments were performed at four time points: before induction (A), after extubation (F), and at 12 hours (G) and 24 hours (H) post-surgery, with the chest divided into 12 regions for examination.Results: A total of 80 patients selected during the study period in patients were analyzed. Incidence of postoperative atelectasis was 87.5% and each lung ultrasound examination required 12.35 ± 4.68 min. Statistically significant fall in PaO2 was recorded at extubation from baseline and intra-operative values (P < 0.0001). Statistically significant difference was established between change in baseline and post-extubation LUSS to the total volume of fluid given (P = 0.002).Conclusion: Atelectasis was detected in 87.5% of adults after robot-assisted laparoscopic pelvic surgeries using lung ultrasound. Oxygenation decreased significantly post-steep Trendelenburg and extubation. The statistical difference in total IV fluids between patient subgroups with increased lung edema signs is suggestive but does not prove causation.